TECHNOLOGY OF OBTAINING SUPERPHOSPHATE FROM CENTRAL KYZYLKUM PHOSPHORITES WITH A LOW CONTENT OF FREE PHOSPHORIC ACID - Sadriddinovich, Bakhriddinov Nuriddin (The journal of contemporary issues in business and government, 2021)
The article shows a decrease in the amount of free acids of simple superphosphate can be achieved through the use of technology for long-term storage of products, as well as mixing technology using screws.